The role of the state in democratic transformation :Iraq after 2003 as a model (قضايا سياسية, 2024)
Democracy is a process of social and civilizational growth to which countries that try to build their reality rise to it in a sound structure within clear foundations through which the people are given the right to choose the form of the political system that provides an appropriate ground on which to base it and gives them the ability to closely interrelate the components of society . The roots of democracy in Iraq extend to the beginning of The monarchy in 1921 , but there were many military coups that took place and the regime turned into a republic in which any form of democracy was absent .That period ended with a transformation that took place through external military intervention . You cannot consider it natural growth , because there was an external will that imposed the decision with the conviction that there was a will .An internal patriotism seeking a new transformation has interfered with external will that imposed itself on reality , and as a result it is tainted with many problems for which solutions must be found and adherence to the principles of the democratic system in order to achieve a sound democratic transformation